Strategi Manajemen dalam Proses Transformasi Digital di Madrasah Aliyah Negeri Karo - Rheina Sayla; Rustam Rustam (Jurnal Publikasi Ilmu Manajemen, 2026)
This study analyzes management strategies in digital transformation at MAN Karo, covering implementation, resource allocation, and monitoring and evaluation. Using a qualitative method with a narrative approach, data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model and triangulation. The results show that MAN Karo has implemented digital transformation in learning (blended learning, YouTube, PowerPoint, social media) and administration (Serikandi, RDM, Pusaka, faceprint). Resource allocation strategies are carried out systematically through four stages, with the principal as the primary decision-maker and support from BOS funds, the Committee, and the government. Monitoring and evaluation are conducted through digital systems (EMIS, ASN, RDM) and direct supervision, with student involvement through the “Suara MANKA” program and outcome-based assessments. The success of the digital transformation is supported by regular training and the Madaris application. The study concludes that well-planned strategies, visionary leadership, continuous human resource development, and stakeholder participation are key factors in the success of digital transformation in Islamic educational institutions.